1997
DOI: 10.1002/(sici)1520-6823(1997)5:2<81::aid-roi6>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal complications of neutron therapy for prostate cancer

Abstract: The purpose of this study was to investigate the cause of hip complaints following conformal neutron therapy delivered by opposed lateral and oblique anterior ports to treat prostate cancer. Twenty‐seven patients with hip complaints following neutron or mixed neutron and photon therapy for prostate cancer had 34 magnetic resonance imaging (MRI) studies 3–39 (mean 15.3) months following treatment; for comparison, 13 similarly treated patients without hip complaints were imaged 1–32 (mean 13.8) months post‐treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…Radiation injury to normal tissues is believed to be nonspecific and generally to produce no pathognomic changes [5]. However, the combined changes in the parenchyma and vascular tissues [6,7] are thought to characterise the radiation damage to healthy tissues. Changes in the vascular network are thought to cause muscle ischaemia whilst a limited ability to expand, due to connective tissue constraints, is believed to have an effect on the efficacy of muscle contraction [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Radiation injury to normal tissues is believed to be nonspecific and generally to produce no pathognomic changes [5]. However, the combined changes in the parenchyma and vascular tissues [6,7] are thought to characterise the radiation damage to healthy tissues. Changes in the vascular network are thought to cause muscle ischaemia whilst a limited ability to expand, due to connective tissue constraints, is believed to have an effect on the efficacy of muscle contraction [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have found axillary radiation to be a prognostic factor for the development of shoulder morbidity [3,4,11]. Soft tissue changes have been seen from the onset of radiotherapy (dose dependent) to as late as 3 years after the start of radiotherapy [6,7]. MRI studies have shown radiation induced muscle morbidity in cervical cancer [9] and prostate cancer [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Muscle changes were mostly observed after 3 years at the latest after RT 17,18 . In breast cancer, clinical findings have been reported on muscle morbidity of the pectoralis major 17,19 .…”
Section: Introductionmentioning
confidence: 98%